Determinants of parental behavior of fathers of primary school-aged children in Croatia - Hanzec Marković, Ivana; Pavlić, Marija; Brajša-Žganec, Andreja (Anales de Psicología / Annals of Psychology, 2024)
The aim of this study was, following Belsky’s process model of parenting, to examine certain individual characteristics of the child (gender, age), individual characteristics of the father (personality traits) and contextual sources of stress and support (relationship satisfaction) as possible determinants of paternal behavior. In addition, the mediating role of relationship satisfaction in the relationship between personality traits and paternal practices was examined. Participants were 988 fathers (Mage = 43.66, SD = 5.41), whose at least one child was between the ages of 8 and 13. The Parental Behavior Questionnaire (URP29), the IPIP15 Personality Questionnaire and the Marriage/Relationship Satisfaction Scale were used. The results showed that paternal support was directly positively predicted by Extraversion; both directly and indirectly, through relationship satisfaction, positively predicted by Consciousness, Agreeableness, and Intellect, and only indirectly negatively predicted by Neuroticism. Together, these predictors explained 36.2% of the paternal support variance. Paternal restrictive control was negatively predicted by the child’s age and gender, Consciousness and Agreeableness (with these personality traits having only small indirect effect through relationship satisfaction), and positively predicted by Neuroticism (with both direct and small indirect effect). A total of 12.3% of the paternal restrictive control variance was explained by these predictors. This study provides information about parenting, especially fathers’ behavior, in a less researched period of child development.